THE INFLUENCE OF WORDWALL MEDIA ON THE LEARNING OUTCOMES OF GRADE III STUDENTS IN SCIENCE LEARNING CHANGES IN THE FORM OF OBJECTS - Aini Soraya Tosari; kasriman (Jurnal Cakrawala Pendas, 2024)
Examining the impact of Wordwall Media on the Academic Performance of Third Grade Science Students at SDN Tanah Baru 1 in the 2023–2024 School Year is the primary objective of this research. The study employed a quantitative approach and a quasi-experimental design for its methodology. Classes III A and B will serve as the experimental and control groups, respectively, in this sampling strategy. Using point biserian correlation, we tested the validity of up to 30 multiple-choice questions; 20 of them passed, while 10 did not. The scientific learning outcomes instrument was deemed "Reliable" after the reliability test using the KR-20 formula yielded a Rhitung value of 5.4361, which is more than the critical reliability value of 1.6972. We may infer that H0 is rejected and H1 is accepted because, according to the results of the t-test, Thitung > Ttabel = 0.975 > 0.564 at a significant level α = 0.05 and egress of freedom (DK) = 30, we get an Effect of Wordwall Media on the Learning Outcomes of Class III Students Learning Science Changes in the Form of Objects at SDN Tanah Baru 1 Depok West java.